Organic marketing communication strategy on the Instagram account @twntynine.str in increasing product sales (BIS Humanities and Social Science, 2026)
This study examines how small businesses can increase product sales on Instagram through organic marketing communication without relying on paid promotions. Many small businesses have limited budgets, which restricts their ability to use paid advertising. Therefore, they must find alternative ways to reach audiences, build brand awareness, and grow sales sustainably. The study focuses on the Instagram account @twntynine.str, which uses authentic content, customer interaction, and storytelling to promote its products organically. @twntynine.str Instagram account uses an organic approach based on personal closeness, consistency in the narrative of the business owner’s journey, and the use of authentic testimonials as key social proof. This approach makes communication feel more natural and emotional, thereby building customer trust, while also creating a point of difference among competitors who prioritize paid promotional tactics, giveaways, or collaborations with Key Opinion Leaders (KOLs). It aims to understand how these strategies are implemented, which elements are most effective, and how they influence sales growth. A qualitative descriptive approach was used, including case studies and in-depth interviews with the owner, administrator, and customers. Data were collected through interviews, documentation, and content analysis. The findings show that @twntynine.str effectively applies an organic marketing strategy by emphasizing authentic content, fast responses, customer testimonials, and emotional engagement, resulting in significant sales growth without paid advertisements. The study concludes that organic marketing communication on Instagram is an effective, low-cost strategy for small businesses to build trust and loyalty and increase sales.